Functional characterisation of twelve terpene synthases from actinobacteria - Chhalodia, Anuj K.; Xu, Houchao; Tabekoueng, Georges B.; Gu, Binbin; Taizoumbe, Kizerbo A.; Lauterbach, Lukas; Dickschat, Jeroen S. (Beilstein Journal of Organic Chemistry, 2023)
Fifteen type I terpene synthase homologs from diverse actinobacteria that were selected based on a phylogenetic analysis of more than 4000 amino acid sequences were investigated for their products. For four enzymes with functions not previously reported from bacterial terpene synthases the products were isolated and their structures were elucidated by NMR spectroscopy, resulting in the discovery of the first terpene synthases for (+)-δ-cadinol and (+)-α-cadinene, besides the first two bacterial (−)-amorpha-4,11-diene synthases. For other terpene synthases with functions reported from bacteria before the products were identified by GC–MS. The characterised enzymes include a new epi-isozizaene synthase with monoterpene synthase side activity, a 7-epi-α-eudesmol synthase that also produces hedycaryol and germacrene A, and four more sesquiterpene synthases that produce mixtures of hedycaryol and germacrene A. Three phylogenetically related enzymes were in one case not expressed and in two cases inactive, suggesting pseudogenisation in the respective branch of the phylogenetic tree. Furthermore, a diterpene synthase for allokutznerene and a sesterterpene synthase for sesterviolene were identified.
Keywords: actinomycetes; biosynthesis; enzymes; NMR spectroscopy; terpenes